Aislamiento y propagación de micelios del hongo comestible nativo Pleurotus ostreatus “Hongo ostra”, en tres variedades de Zea mays, Loreto – Perú - Torres Sánchez, Bruno Gabriel (2024)
The present study was carried out in the city of Iquitos, with the objective of isolating and propagating mycelia of the native edible fungus Pleurotus ostreatus “oyster mushroom”, in three varieties of Zea mays. The mycelial isolation method was used from the reproductive structures of the carpophore of the fungus, using two culture media, Potato Dextrose Agar (PDA) and Malta Extract Agar (MEA) and the mycelial propagation method from the mycelia isolated from three varieties of Zea mays: gallina corn (hard), Polvosara corn (soft) and popcorn (bursting). It was possible to isolate the Pleurotus ostreatus “oyster mushroom” strain in the two-culture media and propagate the mycelia in the three varieties of Zea mays; however, the ANOVA does not show statistical significance.